PENERAPAN METODE CTL DALAM PEMBELAJARAN KARANGAN DESKRIPSI SISWA KELAS IX SMP NEGERI 2 PALU - Siti Hadija Alaydrus (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2021)
The problem in the main research is "How is the application of the CTL method in learning descriptive essays for third grade students of SMP Negeri 2 Palu?". While the objectives to be achieved in this study are to describe the application of the CTL method in learning descriptive essays for third grade students of SMP Negeri 2 Palu. To get the data, the researcher used the technique of literature study, observation, interviews and questionnaires by focusing on learning descriptive essays that were connected to the CTL method used by the teacher in the classroom. The data analysis was carried out in 3 (three) stages, namely (1) data preparation, (2) data processing, (3) data presentation. The results of the study prove that the application of the CTL method in learning descriptive essays for third grade students of SMP Negeri 2 Palu has been running according to the concepts contained in the CTL method. Meanwhile, the components of CTL used by teachers in the field of Indonesian language studies in class III SMP Negeri 2 Palu in learning descriptive essays are Inquiry, Questioning, Constructivism, Community Learning, Authentic Assessment, Reflection and Modeling